Malakoplakia of the Pancreas with Simultaneous Colon Involvement: Case Report and Review of the Literature - Surya Guha; Haiyan Liu (Case Reports in Pathology)
Although malakoplakia has been reported to occur at various body sites, pancreatic malakoplakia with simultaneous colonic involvement is very rare. Lesions of malakoplakia can masquerade as tumor masses leading to unwanted resections. Nevertheless, malakoplakia can occur in association with frank carcinomas, especially in the colon. By reporting a case of pancreatic malakoplakia diagnosed by fine needle aspiration cytology, this paper aims to describe cytologic features of malakoplakia and to further review findings from previous reported cases of pancreatic malakoplakia in the literature. With advances in minimally invasive, image-guided aspiration technologies, cytomorphological analyses can diagnose lesions of malakoplakia. This may help avoid surgeries that would have otherwise been carried out due to a misleading impression of tumor. However challenges remain as to the further management of patients diagnosed with this condition. More studies are necessary to determine the probability of malignancies arising in association with malakoplakia, in order to devise appropriate treatment protocols.